TEACHING SPEAKING THROUGH DIGITAL INSTRUCTIONAL MEDIA - Helfany Amsa; Safriyani Novitri; Sherly Franchisca; Jumerli Ariati (J-Shelves of Indragiri (JSI), 2025)
This study discusses the use of digital instructional media to improve students' speaking skills in teaching speaking skills. Student’s problem in speaking is having limited vocabulary and shy to speak English. The TALK application is an application that can be used in teaching speaking. This aims to improve students' understanding of vocabulary, pronunciation and grammar. This article will discuss the impact of teaching speaking skills through the implementation of the TALK application on teaching speaking and provide learning media that are useful in improving students' speaking skills. The method used in this study is descriptive research. Participants in this study consisted of 40 students from Sport Study Program who took English courses. The results of this study found that the use of the TALK application is efficient to be taught in teaching speaking skills